2020
DOI: 10.1002/esp.5009
|View full text |Cite
|
Sign up to set email alerts
|

Internal erosion of soil pipes: Sediment rating curves for soil pipes

Abstract: The collapse of soil pipes due to internal erosion can result in fully mature gullies. Few studies have measured the rates of sediment detachment and transport through soil pipes in situ. The objectives of this work were to determine suspended sediment concentration (SSC) in soil pipes as a function of pipeflow rate to develop sediment rating curves (SRC) and measure the bedload transport as a function of cumulative flow per storm event. H‐flumes were installed in seven discontinuous gullies formed by pipe col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Underscoring the importance of hydrology and soil erodibility, recent research has identified soil saturation as a cause of piping erosion through loss of soil cohesion (Bernatek-Jakiel et al, 2020). Consistent with that finding, soil pipe sediment yields have been found to be dependent on detachment rather than on runoff rate; and on supply rather than transport capacity (Wilson et al, 2020). The erodibility of some soils means that rain splash can be a significant contributor to gully sediment yields (Crouch & Blong, 1989;Daley et al, 2023).…”
Section: Is Gully Research Good Enough To Inform Management and Preve...mentioning
confidence: 85%
“…Underscoring the importance of hydrology and soil erodibility, recent research has identified soil saturation as a cause of piping erosion through loss of soil cohesion (Bernatek-Jakiel et al, 2020). Consistent with that finding, soil pipe sediment yields have been found to be dependent on detachment rather than on runoff rate; and on supply rather than transport capacity (Wilson et al, 2020). The erodibility of some soils means that rain splash can be a significant contributor to gully sediment yields (Crouch & Blong, 1989;Daley et al, 2023).…”
Section: Is Gully Research Good Enough To Inform Management and Preve...mentioning
confidence: 85%
“…There have been few attempts to identify the sources of cohesion in the soil (Wilson et al 2020). Xue et al (2019) and Bernatek-Jakiel et al ( 2020) identified soil organic carbon as the major cohesion source, with some contribution from Fe and Al oxides and hydroxides.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining 3–30% of cohesion after 10% HCl leaching is most likely caused by organic matter as the only remaining major source of cohesion (c. f. Le Bissonnais, 1996; Xue et al, 2019). There have been few attempts to identify the sources of cohesion in the soil (Wilson et al 2020). Xue et al (2019) and Bernatek‐Jakiel et al (2020) identified soil organic carbon as the major cohesion source, with some contribution from Fe and Al oxides and hydroxides.…”
Section: Discussionmentioning
confidence: 99%